Anticancer Activity of Calotropis procera by Molecular Docking Analysis - Krithika Vasanth Naik; Nilofar Khan (International Journal of Biochemistry and Biomolecule Research, 2024)
Cyclin-dependent kinase 2 (CDK2) is a protein synthesized by Calotropis procera. It is known to be responsible for causing cancer in the human body. Studies have presented the significance of the phytochemicals to inhibit the CDK2 protein. Adsorption, distribution, metabolism, and excretion (Swiss ADME) and PubChem were the pharmacological tools which were used to check molecular weight, which should be less than 500D, acceptors less than 10, and donors less than 5, Log P less than 5 and gastrointestinal (GI) absorption should be high and Blood Bank Barrier (BBB) is also identified. If the drug-likeness is absent and has 2 violations then there will be no drug discovery. Using PubChem, the ligands were searched and the Simplified molecular-input line-entry system (SMILES) was copied and pasted to the list of smiles box in Swiss ADME and ran the process. From that, we come to know the molecular weight, acceptors, donors log p values, etc. By using a protein data bank (PDB) we got a PDB ID for CDK2 protein, i.e., 5NEV. Later 3d ligand binding site and active site prediction for protein was identified. The total ligands used here are 5 and they are calotropagenin, anthraquinone, flavonoid (ternatin), coumarin, and cannogenin. Then all the ligands were cleaned using Marvin's sketch. Energy minimization of protein was done by using the Swiss PDB viewer and then the PyRx tool (Visualization tool) was used to check the least binding affinity of the ligands. From the 5 ligands one which has the least binding affinity is taken for the docking process. Here, the ligand which is having least binding affinity is anthraquinone which is bound to the CDK2 protein. And later the docking visualization was performed using Biovia Discovery Studio and AutoDock Tools-1.5.6.
Keywords: Anticancer activity; Cyclin-dependent kinase 2 protein; Lipinski rule; Ramachandran plot; anthraquinone